Identificação de DNA de Leishmania sp. no encéfalo de cães com Leishmaniose visceral - Cardinot, Cinthya Brillante [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
There are few reports of neurological disorders in dogs with visceral leishmaniasis, with or without the participation of other opportunistic agents. The aim fo the present study was to investigate, by Real Time PCR, the presence of Leishmania sp. in the brain of dogs naturally affected by visceral leishmaniasis (VL). We evaluated 24 dogs with VL, of whom two were asymptomatic and two had also neurological symptoms. DNA was amplified in the brain of 23/24 (95.8%) dogs. The parasite load ranged from 2-16964 amastigotes/mL with a median of 116 parasites/mL and mean and standard deviation of 1166 ± 3546 parasites/mL. The average number of parasites in dogs with VL with neurological disorders, in dogs without neurological alterations and in asymptomatic dogs were, respectively, 2010, 1119 and 772 parasites/mL. These results demonstrate that the parasite has the ability to penetrate into the nervous system and should contribute to the development of neurological lesions
Keywords: Leishmania; Reação em cadeia de polimerase; Sistema nervoso central; Cão; DNA; Manifestações neurológicas de doenças; Real time PCR